A keyword-based organizing framework for ERP intellectual contributions. Issue 5 (14th September 2015) - Fadlalla, Adam; Amani, Farzaneh
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to develop a keyword-based organizing framework for enterprise resource planning (ERP) intellectual contributions, and use the proposed framework to derive major areas of emphasis in ERP research. Design/methodology/approach – Using keyword persistence, a time-based measure, and keyword dominance, a frequency-based measure, the authors constructed an empirical framework to classify ERP intellectual contributions. Findings – Four major ERP themes were identified using the proposed framework; namely, emerging/phantom, intermittent, trendy, and core. Further examination of the keywords in each of these themes revealed that whereas the business aspects of ERP systems are discussed in an intermittent manner, its technical aspects are discussed in a trendy fashion. Research limitations/implications – The main limitation of this research is that it only used keywords from papers published in scholarly journals, and did not include conference proceedings, books, and other outlets. In this paper, the authors developed an objective keyword-based organizing framework. The proposed framework is simple, flexible, and is based on dimensions that are research domain independent, and thus can be used as an organizing framework for any research domain. Practical implications – The proposed framework may help managers to better focus consulting engagements on ERP implementations through identifying areas that are not well covered by researchers to ensure that such areas they are well covered by consulting services. Originality/value – The main contribution of this paper is the development of an objective keyword-based framework that can be used as an organizing tool for intellectual contributions. The framework can be used to derive insights in the macro characterizations of the research in a given domain, and is thus valuable to researchers – both academic and practitioner. To the best of the authors' knowledge, this is the first such keyword-based research organizing framework.